2022
DOI: 10.1088/1742-6596/2334/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Design of cobalt nickel nitrides/carbon nitride composite catalysts for enhanced electrochemical water splitting

Abstract: Design of efficient non-noble metal electrocatalysts for oxygen evolution reaction (OER) have been considered as a crucial issue in the development of future renewable energy utilization. In this paper, we report a composite structure of cobalt nickel nitrides and carbon nitrides as efficient OER electrocatalysts. A facile hydrothermal method was utilized to synthesize the precursors, then the samples were treated with melamine and heated in an N2 atmosphere. The successful preparation of the cobalt nitride ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In this regard, Ji et al reported the fabrication of cobalt nickel nitrides/g‐C 3 N 4 composite for electrochemical OER process. [ 123 ] A facile hydrothermal method was utilized to prepare these composite electrodes. This Co 2 NiN/g‐C 3 N 4 electrode exhibited an optimal electrocatalytic performance with an over potential of 0.62 V at current density of 10 mA cm −2 , which is lower than Co 2 NiN or g‐C 3 N 4 individuals.…”
Section: Interface Engineering Of G‐carbon Nitridementioning
confidence: 99%
“…In this regard, Ji et al reported the fabrication of cobalt nickel nitrides/g‐C 3 N 4 composite for electrochemical OER process. [ 123 ] A facile hydrothermal method was utilized to prepare these composite electrodes. This Co 2 NiN/g‐C 3 N 4 electrode exhibited an optimal electrocatalytic performance with an over potential of 0.62 V at current density of 10 mA cm −2 , which is lower than Co 2 NiN or g‐C 3 N 4 individuals.…”
Section: Interface Engineering Of G‐carbon Nitridementioning
confidence: 99%
“…In the current situation of China's cobalt import and export trade, we need to understand China's position in the world cobalt trade pattern more, and the rise of the complex network analysis method facilitates better use of dynamic data to study the evolution characteristics of the world cobalt trade pattern []- [22]. As a traditional Chinese trade product in trade, cobalt trade occupies a pivotal position in Chinese product trade [23]. China's cobalt trade has a long history, and reviewing China's economic development in recent years, and it can be said that the development of the cobalt export trade economy has been a great challenge to its influence in the international market []- [26].…”
Section: Introductionmentioning
confidence: 99%